Strengthening the Profile of Pancasila Students Through Project-Based Learning - Nanang Faisol Hadi; Muhammad Nasir; M. Tahir (SYAMIL: Journal of Islamic Education, 2023)
The development of the times requires all elements of life to adapt, including the world of education. He is required to be more sensitive, creative and innovative. One form of this adjustment is student-centered learning in the form of project-based learning. This research uses a qualitative approach with the type of research being a case study. Researchers investigated in depth, understood and described facts about strengthening the profile of Pancasila students through project-based learning. Data was obtained through observation, interviews and documentation. Meanwhile, data analysis uses the techniques described by Miles and Huberman, data reduction, data presentation, and data verification. The results of this research show that: 1). Planning consisting of forming a project team, choosing a general theme, determining the topic, determining the dimensions, elements and sub-elements of the Pancasila student profile, and compiling teaching modules, 2). Implementation, consisting of conducting socialization with students' parents, carrying out student-centered learning, teachers always guiding students, varying learning activities, and holding learning celebrations or exhibitions, 3). Post-learning consists of students' work, reflection, evaluation, and students' new understanding of issues related to the chosen themes and topics.